1949
DOI: 10.1021/jo01158a015
|View full text |Cite
|
Sign up to set email alerts
|

The Interchange Reaction of Vinyl Acetate With Organic Acids

Abstract: The reaction of vinyl acetate with carboxylic acids in the presence of mercuric salts of strong acids as catalysts to form the vinyl ester of the acid was first reported by Hermann and Haehnel (1) and Toussaint and MacDowell (2).This reaction, which we will call the "Vinyl Interchange" Reaction, to differ-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
36
0

Year Published

1963
1963
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(36 citation statements)
references
References 4 publications
0
36
0
Order By: Relevance
“…In order to investigate the efficiency of enzymatic acylation of flavonoid glycosides with natural aryl propenoic acids, vinyl esters of cinnamic, ferulic, and coumaric acids were purchased or prepared according to the general method available (Adelman, 1949;Swern and Jordan, 1963;Hopff and Osman, 1968). Initially, the acylations were carried out on a few mg scale to assess the progress of the reaction and to select particular substrate combinations for preparative scale synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…In order to investigate the efficiency of enzymatic acylation of flavonoid glycosides with natural aryl propenoic acids, vinyl esters of cinnamic, ferulic, and coumaric acids were purchased or prepared according to the general method available (Adelman, 1949;Swern and Jordan, 1963;Hopff and Osman, 1968). Initially, the acylations were carried out on a few mg scale to assess the progress of the reaction and to select particular substrate combinations for preparative scale synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…Vinyl acetate [108-05-4], CH 3 CO 2 CH¼CH 2 , M r 86.09, is a colorless, flammable liquid with a characteristic, slightly pungent odor, bp 72. 8 C, density at 20 C 0.932 g/mL, mp À 93.2 C, viscosity 0.43 mPA Á s, vapor pressure 12 kPa at 20 C, 42.6 kPa at 50 C, coefficient of cubic expansion 0.0014 K À1 , flashpoint À 8 C, ignition temperature 385 C. Lower/upper flammability limits in air 2.3/13.4 vol %, ignition group (VDE 0165) G 2, specific heat 1.926 kJ/kg; heat of evaporation 379.3 kJ/kg at 72.7 C, heat of combustion 2082.0 kJ/mol, refractive index n acetic acid [11] (see also Section 2.3) and with alcohols gives the corresponding acetate and acetaldehyde. Thermal cleavage gives ketene and acetaldehyde [12].…”
Section: Propertiesmentioning
confidence: 99%
“…Adelman [6] studied vinyl esterification reaction using mercuric acetate(II) based on infrared absorption spectrum. Kavitha et al [7] reported the synthesis of vinyl caffeate with low yield.…”
mentioning
confidence: 99%